'Remembering as Forgetting': Organizational commemoration as a politics of recognition. Issue 2 (February 2019) - Cutcher, Leanne; Dale, Karen; Tyler, Melissa
This paper considers the politics of how organizations remember their past through commemorative settings and artefacts. Although these may be seen as 'merely' a backdrop to organizational activity, they form part of the lived experience of organizational spaces that its members enact on a daily basis as part of their routes and routines. The main concern of the paper is with how commemoration is bound up in the reflection and reproduction of hierarchies of organizational recognition. Illustrated with reference to two commemorative settings, the paper explores how organizations perpetuate a narrow set of symbolic ideals attributing value to particular forms of organizational membership while appearing to devalue others. In doing so, they communicate values that undermine attempts to achieve equality and inclusion. Developing a recognition-based critique of this process, the discussion emphasizes how commemorative settings and practices work to reproduce established patterns of exclusion and marginalization. To this end, traditional forms of commemorative portraiture that tend to close off difference are contrasted with a memorial garden, in order to explore the potential for an alternative, recognition-based ethics of organizational commemoration that is more open to the Other.